On some Linyphiidae of China, mainly from Taibai Shan, Qinling Mountains, Shaanxi Province (Arachnida: Araneae) - Tanasevitch, Andrei V. (Zootaxa, 2006)
The collection of Prof. J. Martens and, in part, of Dr P. Jäger, mainly from Taibai Shan, Qinling Mountains, Shaanxi Province, China, contains 36 identifiable species of Linyphiidae. Among these, the following nine new species belong to known genera: Agyneta martensi sp. n., Arcuphantes chinensis sp. n., Indophantes ramosus sp. n., Mughiphantes beishanensis sp. n., M. jaegeri sp. n., M. martensi sp. n., Nippononeta sinica sp. n., Asthenargus conicus sp. n., and Dicymbium sinofacetum sp. n. Each of the remaining five new species warrants the erection of a new genus: Houshenzinus gen. n. (type species: Houshenzinus rimosus sp. n.), Shaanxinus gen. n. (type species: Shaanxinus rufipes sp. n.), Shanus gen. n. (type species: Shanus taibaiensis sp. n.), Taibainus gen. n. (type species: Taibainus shanensis sp. n.) and Taibaishanus gen. n. (type species: Taibaishanus elegans sp. n.). The following new synonym and combinations are proposed (valid names on the right): Gnathonarium cambridgei Schenkel 1963 = Gnathonarium taczanowskii (O. Pickard-Cambridge 1873) syn. n., Araeoncus stigmosus Xia, Zhang, Gao, Fei, Rui & Kim 2001 = Tibioploides stigmosus (Xia, Zhang, Gao, Fei, Rui & Kim 2001) comb. n., Walckenaeria anguilliformis Xia, Zhang, Gao, Fei, Rui & Kim 2001 = Shaanxinus anguilliformis (Xia, Zhang, Gao, Fei, Rui & Kim, 2001) comb. n., and Lepthyphantes huangyuanensis Zhu & Li 1983 = Tchatkalophantes huangyuanensis (Zhu & Li 1983) comb. n. The female of Tibioploides stigmosus comb. n. is described for the first time.